Continuous thermosalinograph oceanography along RV METEOR cruise track M176 - Jörg Geldmacher; Michael Schlundt (PANGAEA, 2022)
Underway temperature and salinity data was collected along the cruise track with two autonomous thermosalinograph (TSG) systems, each consisting of a SBE21 TSG together with a SBE38 Thermometer. Both systems worked independent from each other throughout the cruise. While temperature is taken at the water inlet in about 5 m depth, salinity is estimated within the interior TSG from conductivity and interior temperature.